Measures of Post Covid-19 Pandemics in Hospitality and Tourism Industries - Bastola, Dipak (Research Nepal Journal of Development Studies, 2020)
The study entitled, Measures of post Corona virus pandemics in hospitality and tourism industries, aims to find the impact of the occurrence of corona virus on the tourism industry in Nepal and its preventive measures. The objective of the study is to collect the programmatic ideas to reduce the negative impacts of COVID-19 in Nepalese Tourism and Hospitality Industries. The secondary research methodology- predominantly secondary data has been used- has been implemented for the research. Several pieces of literature, journal articles, research or thesis paper, government documents, etc., are considered to collect the necessary information for the study. For data collection, the secondary data has been collected through extensive literature reviews. In conclusion the need of the hours is to function all stakeholders of this sector in collaborative and coordinated manner not only to mitigate the repercussions of this volatile pandemic but also to formulate short-term, mid-term and long term plans to ease the recovery.